Microvascular Decompression for Trigeminal Neuralgia Caused by Venous Offending on the Ventral Side of the Root Entrance/Exit Zone: Classification and Management Strategy - Wang, Wenhua; Yu, Feng; Kwok, Sze Chai; Wang, Yuhai; Yin, Jia (Frontiers in Neurology, 2022)
Background: Trigeminal neuralgia (TGN) is typically caused by offending arteries (OA), but may also involve offending veins. Venous offending inside of the root entrance/exit zone (VOIR) is particularly challenging. Objective: To analyze the pattern, rate of VOIR and propose management strategy accordingly. Methods: VOIR was classified into 3 types based on the anatomical relationship (A, the entire route of the vein was covered by the nerve root; B, the vein was lateral to the nerve root; and C, the vein penetrated the nerve root) and 3 grades based on the importance of VOIR to neurovascular conflict (I, no OA; II, suspected OA; and III, definitive OA). Results: The analysis included 143 cases with complete follow-up. Type A, B and C accounted for 11.9%, 31.5% and 56.6% of the cases, respectively. Grade I, II and II accounted for 24.5%, 26.6% and 49.0%, respectively. Most grade I VOIR cases (26 out of 31) were managed with coagulation followed by division. Most grade II VOIR cases (31 out of 38) were decompressed with shredded Teflon interposition. Grade III VOIR was left in place in all 70 cases. Initial Pain relief was achieved in all cases. Twenty one patients (14.7%) experienced varying degrees of temporary hemifacial hypesthesia, appearing at the patients decompressed with Teflon mostly (14/21). Within 4.5-year median follow-up, pain recurred partly in 11 patients (7.7%). Conclusion: VOIR is not uncommon in patients with TGN. To satisfying outcomes, different management strategy should be chosen according to the type and grade of VOIR.